Safeguarding Mobile Users from Violation by Third-party Apps - Vusumuzi Malele; Kagiso Mphasane (Latin-American Journal of Computing)
Insecure third-party mobile applications (apps) can have a detrimental impact on mobile users in terms of information security and data privacy. Insufficient protection for third-party mobile apps platforms may result in harmful installations. The purpose of this paper was to make recommendation on guidelines for safeguarding mobile users from violations by third-party apps. In this regard, empirical data was collected through questionnaires developed to determine the necessary themes that led to the development of the recommendations. The findings showed that a large percentage of participants are not aware of basic security methods to safeguard themselves. Secondly, there is a need for increased confidence in data integrity protocols, and the necessity to ability for emphasizing strong availability controls and backup strategies for mobile users’ continuous access to services. Since the findings align to the Confidentiality, Integrity, and Availability (CIA) triad framework, then the recommendations were made as an implementation strategy of the CIA triad for safeguarding mobile users against violation by the third-party apps. Mobile users will benefit immensely on the recommendations as empower them as the first line of defense against cybercrimes.